Spatial patterns of Aquificales in deep-sea vents along the Eastern Lau Spreading Center (SW Pacific) - Ferrera, Isabel; Banta, Amy B; Reysenbach, Anna-Louise (SYSTEMATIC AND APPLIED MICROBIOLOGY, 2014)
The microbial diversity associated with actively venting deep-sea hydrothermal deposits is tightly connected to the geochemistry of the hydrothermal fluids. Although the dominant members of these deposits drive the structure of the microbial communities, it is less well understood whether the lower abundance groups are as closely connected to the geochemical milieu, or driven perhaps by biotic factors such as microbial community interactions. We used the natural geochemical gradients that exist in the back-arc basin, Eastern Lau Spreading Center and Valu-Fa Ridge (ELSC/VFR) in the Southwestern Pacific, to explore whether the chemolithotrophic Aquificales are influenced by geographical location, host-rock of the vent field or deposit type. Using a combination of cloning, DNA fingerprinting (DGGE) and enrichment culturing approaches, all genera of this order previously described at marine vents were detected, i.e., Desulfurobacterium, Thermovibrio,Aquilex, Hydrogenivirga, Persephonella and Hydrogenothermus. The comparison between clone libraries and DGGE showed similar patterns of distribution of different Aquificales whereas results differed for the enrichment cultures that were retrieved. However, the use of cultivation-based and -independent methods did provide complementary phylogenetic diversity overview of the Aquificales in these systems. Together, this survey revealed that the ELSC/VFR contains some of the largest diversity of Aquificales ever reported at a deep-sea vent area, that the diversity patterns are tied to the geography and geochemistry of the system, and that this geochemical diverse back-arc basin may harbor new members of the Aquificales. (C) 2014 Elsevier GmbH. All rights reserved.
Keywords: ROV Jason (Remotely Operated Vehicle)